2018
DOI: 10.1364/boe.9.001648
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying optical properties with visible and near-infrared optical coherence tomography to visualize esophageal microwave ablation zones

Abstract: Abstract:Microwave ablation is a minimally invasive image guided thermal therapy for cancer that can be adapted to endoscope use in the gastrointestinal (GI) tract. Microwave ablation in the GI tract requires precise control over the ablation zone that could be guided by high resolution imaging with quantitative contrast. Optical coherence tomography (OCT) provides ideal imaging resolution and allows for the quantification of tissue scattering properties to characterize ablated tissue. Visible and near-infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…At the beginning of laser exposure, laser beam irradiation results in the formation of blisters that later collapse. In previous studies, it was demonstrated that the tissue temperature was proportional to the exposure time and that the scattering coefficient increased with temperature [36], [37]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 77%
“…At the beginning of laser exposure, laser beam irradiation results in the formation of blisters that later collapse. In previous studies, it was demonstrated that the tissue temperature was proportional to the exposure time and that the scattering coefficient increased with temperature [36], [37]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 77%
“…There is a growing interest in producing and utilizing 3D maps of the attenuation coefficient [21,32]. For example, depth-resolved attenuation coefficient maps have already been employed to investigate various tissues, including atheroscletertic [33], brain [20], and esophageal [34]. These depth-resolved methods are still vulnerable to the limitations discussed previously, namely the restriction to low-NA lenses and difficulty in precisely specifying the position of focus.…”
Section: Discussionmentioning
confidence: 99%